The gut-adipose tissue crosstalk: unravelling the mechanisms of ghrelin-mediated regulation of adipose tissue angiogenesis - Silva, Daniela Rosendo da (2020)
Dissertação de Mestrado em Biologia Celular e Molecular apresentada à Faculdade de Ciências e Tecnologia